Predictability Study of Warm-sector Convective Event over the Middle-lower Reaches of the Yangtze River： Based on Convection-allowing Ensemble Simulation - Yuan XU; Jinzhong MIN; Xiaoran ZHUANG (Gaoyuan qixiang, 2022)
Warm-sector torrential rainfall event under the background of weak synoptic-scale forcing is difficult to predict accurately due to less knowledge on its initiation and development mechanism.In order to further investigate the practical and intrinsic predictability of warm-sector convective event over the middle-lower reaches of the Yangtze River （MLRYZ）， a convection-allowing ensemble forecast （CaEF） system based on WRF-EnSRF is constructed by using ensemble data assimilation which assimilates the radiosonde and radar simulation data simulated from the convection-allowing model.An initial perturbation ensemble experiment is conducted for a typical warm-sector convective event on 21 July 2013， and the experimental results show that there are two bifurcation stages with significant differences in convection initiation time and precipitation location among ensemble members.The first bifurcation is related to interaction between perturbed planetary boundary layer wind field and mesoscale topography in convection initiation stage， while the second in convection development stage is due to the difference of convective system intensity caused by initial perturbations.Strong （weak） convection and strong （weak） outflow from cold pool could lead to a south （north） precipitation area.Further predictability analysis based on quantitative method suggests that the practical predictability at bifurcation stages is strongly limited reflected by rapid growth in precipitation field variation （both time and space） and difference total energy （DTE）.Additionally， nonlinear characteristic between difference total energy curves in identical-twin experiments reducing the amplitude of initial perturbations reveals a more serious limit of intrinsic predictability during convection initiation stage （the first bifurcation stage） than other times.The significant sensitivity mode on ensemble sensitivity analysis （ESA） also shows that the error of planetary boundary layer wind field has an important influence on both practical and intrinsic predictability in this event， which is consistent with the cause of two bifurcation stages.In conclusion， the accurate initial condition could effectively improve the prediction effect when the practical predictability of model in bifurcation stages is limited by initial perturbations （errors）.However， when the weather process is limited by the intrinsic predictability caused by chaotic nonlinear dynamics， the prediction effect promotes finitely by improving initial condition， and the need for ensemble （probability） forecast is especially highlighted in such situation.The above research not only helps to understand the predictability of warm-sector convective event over the middle-lower reaches of the Yangtze River， but also provides suggestions on designing appropriate convection-allowing initiation perturbations and establishing target observations according to the corresponding bifurcation characteristics.